A facile way to prepare mesoporous spherical calcites controlled by chondroitin sulfate for shape and carboxymethyl chitosan for size. Issue 44 (21st October 2016) - Liu, Xujie; Elkhooly, Tarek A.; Huang, Qianli; He, Wei; Cai, Qiang; Feng, Qingling; Mi, Shengli
Abstract : Spherical calcites with a mesoporous structure were obtained with the cooperative role of two polymers: chondroitin sulfate and carboxymethyl chitosan. Abstract : Inspired by biomineralization, monodispersed spherical calcites coated with a layer of polymer were obtained with the cooperative role of two polymers: carboxymethyl chitosan for size control and chondroitin sulfate for shape control. These calcites can be regarded as mesocrystals aggregated by nanoparticles with a mesoporous structure, and therefore have potential application as drug delivery systems.